Humanized care for critically ill patients in Urgent and Emergency care units (International Seven Journal of Multidisciplinary, 2024)
To show the importance of the role of health professionals in providing care and humanized assistance in Urgent and Emergency Care Units. The chosen methodology was bibliographical research, of the integrative literature review type, and the search for manuscripts was carried out on the electronic pages: SCIELO, VHL, LILACS and MEDLINE, limiting those published between the years 2018 to 2022. Studies have shown that humanized assistance is of great relevance in urgent and emergency services and should have as its main objective the promotion of the patient's well-being, taking into account not only their clinical status, but also their emotional and mental health. their family members. These results are part of a search that found 142 articles, of which 29 were excluded for not meeting the research objective, 18 were excluded for being in English or Spanish, 34 were incomplete, 46 did not meet the time frame from 2018 to 2022 , with only 15 remaining included in the final sample of this review. Of these, 15 (100%) were in Portuguese, 06 (40%) are from 2018, 05 (33.33%) are from 2019, 01 (6.67%) are from 2020 and 03 (20%) are from 2021. Through the studies analyzed, it is concluded that even in the face of all the difficulties encountered, humanization and assistance in care, especially in the urgency and emergency sectors, are of great importance for all work performed to take place satisfactorily offering a quality service, trust, dignity and respect for human beings.